Incidental Carcinoma Gall Bladder in Patients Undergoing Cholecystectomy for Chronic Calculus Cholecystit is - Biswas, PK; Das, PK; Rahman, MH; Mahanta, DK (TAJ: Journal of Teachers Association, 2009)
Carcinoma gall bladder (CaGb) is the most common neoplasm of biliary tract. Aetiology of this tumour is complex, but there is a strong association with gall stones. The symptoms are seldom suggestive of cancer and imaging techniques are usually equivocal. This study was conducted to see the frequency of cancer of gall bladder in patients undergoing surgery for chronic cholecystitis with cholelithiasis in different age and sex groups in our population. An observational study was conducted in the department of surgery unit-II Rajshahi Medical College Hospital and Mukti Clinic Rajshahi on the patients admitted with the diagnosis of chronic cholecystitis with cholelithiasis for surgery. Demographic, clinical presentation, imaging studies, operative intervention and histopathological results were examined. Over the period of 18 months 184 patients were admitted with the diagnosis of chronic calculus cholecystitis for cholecystectomy. 2 (1.09%) patients out of 184 admitted cases were diagnosed as carcinoma gall bladder after histopathology examination. Mean age was 38.5 (41h decade) years and both of them were female. The most common presenting complaints were pain in the right hypocondrium and dyspepsia (51.07%). Normal wall thickness with stone was the most common (63.04%) Ultrasonographic finding. Histologically all CaGb cases were adenocarcinoma. Gall bladder malignancy occurs commonly in 4th decade of life. The patients should be encouraged to have gall bladder surger y once diagnosed as gall stone disease. Every gall bladder specimen should be sent for histopathological examination. TAJ 2009; 22(1): 223-226